Kualitas Pelayanan dan Harga (Price) Mempengaruhi Kepuasan Konsumen pada CV. Angga Trans Lahat - Hestin; Kasinem; Sholiha, Emila; Andayani, Melia (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2025)
The purpose of this research is to determine the influence of service quality and price on consumer satisfaction at CV. Angga Trans Lahat. The variables in this research are Service Quality (X1), Price (X2), and Consumer Satisfaction (Y), The data analysis methods used are instrument Test (Reliability Test, Validity Test, Classic Assumption Test (Normality Test, Heteroscedasticity Test, Multicollinearity Test, Multiple Linear Regression Analysis, Hypothesis Test (T test and F Test), and Coefficient of Determination Test. The research results showed that (1) Service quality has a partially significant effect on consumer satisfaction, this can be seen from the calculated t value > t table (12.723 – 1.986). (2) Price has a partially significant effect on Consumer Satisfaction, this can be seen from the calculated t value > t table (2.030 1.986). (3) Service quality and price have a significant effect simultaneously on consumer satisfaction, this can be seen from the calculated f value of f table ( 129.039 – 3.097) and the significance value is smaller than the significance level (a) 0.05 (0.000 < 0.05. Keywords: service quality, price, consumer satisfaction